Keberhasilan Perekonomian Islam (Sebuah Kajian Historis terhadap Reformasi Ekonomi Umar Bin Abdul Aziz) - Moh. Ihsan Fauzi (ITB AAS INDONESIA Surakarta, 2021)
Umar bin Abdul Aziz was one of the Caliphs of the Umayyads who was able to increase economic productivity with the concept built from Islamic teachings. This study aims to find out how the management of Islamic daulah and economic policies of Umar bin Abdul Aziz in creating the welfare of the people. This research method uses literature review, namely research with the focus of study and analysis of the primary materials of the literature with the approach of character studies, which examines sitematically the thoughts and ideas of Umar bin Abdul Aziz in whole or in part. From the results of this research it is known that Umar bin Abdul Aziz reformed economic policy with the concept of radd al-mazhalim in which he removed all wrongdoing including in the field of trade, agriculture, and sources of state revenue that had an impact on improving the economy. While in the state spending policy, he put the interests of the people first and strictly in the expenditure of official service facilities and stationery, so as not to occur misappropriation and waste.